Reliance, media exposure and credibility - Syed Abdullah Idid, Syed Arabi; Sannusi, Shahrul Nazmi; Arandas, Mohammed Fadel (2019)
This study discusses credibility of both the traditional and social media from the audience perspective. Numerous definitions and conceptualisations of media credibility are either source or medium based but there are also numerous measurements made on the concept that gave rise to varied findings. An attempt was made to associate the concept of credibility with media exposure, postulating that the greater use of media would mean greater credibility. Two studies were made involving a total of 4095 respondents with 1544 questionnaires distributed in April 2019, and 551 questionnaires in January 2018 to investigate the concept of credibility and its correlate with media use. The first period was before the General Elections but the April 2019 study was made after the May General Election giving an idea how credibility could have changed under a new government. The results of this study revealed that Malaysians perceived the traditional media, including TV, radio, and newspapers, were more credible than the new media (internet, online news portals, Facebook, and Twitter). TV was perceived to have the highest credibility, while Twitter, the lowest credibility. The social media suffered low credibility due to the surrounding discussions on fake news, false information, and post-truth issues. The sources of content in the traditional media are mostly known or verified, unlike that of the new media, thus paving for the poor evaluation of credibility of the new media.